(3eTQhY GdEfeGA GdJQHhj, echf (B((3JfejI GdbjGOI(B)s - (3beGWj, EdgGes ((3HjQhJs (3QGHWI CSGJPI GdJYdje GdKGfhj aj dHfGfs, 2007)
(3jJfGhd gPG GdaUd Gge fbGW eOGNdI GdGSJGPI EdgGe beGWj GdPj aUdJ NdGdg eQGMd hCgOGa eTQhY GdGfeGA GdJQHhj (B"(3JfejI GdbjGOI(B".s
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Cycle Secondaire; Leadership; Leadership; Secondary Education; (3GdbjGOIs; (3GdeQMdI GdKGfhjIs